The Effect of Personal Independence and Entrepreneurship Knowledge on the Success of MSMEs in Tambakbaya Village - Mulyatuti, Mulyatuti; Purnamasari, Sulfi (International Journal of Economics Education Research (IJEER), 2022)
This study aims to determine (1) the effect of personal independence on the success of MSMEs in Tambakbaya Village, (2) the effect of entrepreneurship on the success of MSMEs in Tambakbaya Village, and (3) the simultaneous effect of personal independence and entrepreneurship on the success of MSMEs in Tambakbaya Village. This research is a type of quantitative associative research that aims to analyze the influence of one variable with other variables. The sample in this study were all members of the population of MSME actors in Tambakbaya Village, totaling 70 respondents. Primary data was collected through questionnaires and interviews, secondary data was collected through literature study. The data analysis used is descriptive statistical analysis and inferential statistical analysis. The results showed that the variables of personal independence and entrepreneurial knowledge had a positive and significant effect simultaneously on business success. With the obtained F-count value of 204.507 > 3.13 (F-table), the significance value obtained is 0.000 <0.05 and the R Square value is obtained a value of 0.859. Then H0(3) is rejected and H3 is accepted. So it can be interpreted that the variables of personal independence and entrepreneurial knowledge have a positive and significant effect simultaneously on the business success of MSME actors in Tambakbaya Village with a magnitude of 85.9% influence and the remaining 14.1% influenced by other variables that are not in this research. Based on the value of multiple linear regression, the personal independence variable is the variable that most influences the business success of MSME actors in Tambakbaya Village.